Prohibitions on Notary Promotion and Digital Legal Education: Reconstructing Ethical Boundaries in Indonesia - Fahmi Nugraha; Khusnul Yakin; Tahengga Primananda Alfath (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2026)
Advances in digital technology have transformed communication patterns within the legal profession, including the notary profession, thereby blurring the line between legal consultation and the promotion of notary services. On the one hand, notaries have a duty to provide legal consultation as part of their social function; on the other hand, they are bound by a prohibition on promotion aimed at preserving the dignity and independence of the office. This situation creates normative ambiguity and the potential for ethical violations, particularly in the practice of legal consultation via digital media. The purpose of this study is to analyze the normative regulations regarding the prohibition on promotion in the Notary Office Act and the Notary Code of Ethics, as well as to examine the relevance and limitations of their application to legal consultation activities conducted by notaries in the digital age. The research method employed is normative legal research using a juridical, conceptual, and analytical approach. The findings indicate that the prohibition on promotion within the notary profession remains philosophically relevant for preserving the dignity, independence, and public trust in the notary profession. However, in the context of the digital era, existing regulations are not yet fully adaptive, thereby creating a gray area between educational legal counseling and covert promotion. Therefore, a reconstruction of the regulatory framework is necessary through the clarification of normative and ethical boundaries in digital legal counseling, including specific regulations regarding notaries’ digital communication, the strengthening of a digital-based code of ethics, and more responsive oversight mechanisms to technological developments.